Highly Luminescent π‐Conjugated Terpyridine Derivatives Exhibiting Thermally Activated Delayed Fluorescence. Issue 1 (3rd November 2016) - Sasabe, Hisahiro; Hayasaka, Yuya; Komatsu, Ryutaro; Nakao, Kohei; Kido, Junji
Abstract: Typically, luminescent π‐conjugated 2, 2′:6′, 2′′‐terpyridine (tpy) derivatives are versatile components for tridentate metal ligands, supramolecular materials, two‐photon absorption bioimaging probes, fluorescent ion sensors, and organic light‐emitting devices. However, a limited number of luminescent tpy materials, other than metal complexes, have been reported. This study introduces a series of π‐conjugated tpy derivatives that exhibit strong thermally activated delayed fluorescence (TADF). We have observed that a blue tpy emitter outperforms conventional fluorescent emitters. Additionally, a green tpy emitter has exhibited a performance that is almost comparable to that of its green phosphorescent counterparts, realizing an external quantum efficiency close to 25 % and a power efficiency exceeding 80 lm W −1 with an exceptionally low efficiency roll‐off. This study demonstrates the first example of highly luminescent tpy‐based TADF emitters. Abstract : Terpyridine‐based TADF emitters : A series of terpyridine/acridine conjugates has been prepared, the members of which exhibit strong blue‐to‐green emission and thermally activated delayed fluorescence (TADF) character in the solid state. An organic light‐emitting device with a green emissive terpyridine/acridine conjugate shows an external quantum efficiency of close to 25 %, a power efficiency of over 80 lm W −1, and an exceptionally low efficiency roll‐off (see graphic).